Skin Dose Modeling and Measurement in a High Field In-Line MRI-Linac System - Tai, Madiha; Patterson, Elizabeth; Metcalfe, Peter E.; Rosenfeld, Anatoly; Oborn, Bradley M. (Frontiers in Physics, 2022)
The Australian MRI-Linac prototype radiotherapy system has been shown to generate significant entry skin or surface dose increases. This arises from electron contamination focusing toward the isocenter caused by the 1 T MRI field being in-line with the x-ray beam. The aim of this study is to present accurate Monte Carlo modeling of these skin dose changes and to compare them with previous experimental measurements. Accurate skin dose modeling will improve confidence in the pathway forward to treatment planning for clinical trials. A COMSOL Multiphysics model of the Australian MRI-Linac system was used to generate a 3D magnetic field map to be used in corresponding Geant4 Monte Carlo simulations. The Geant4 simulations included the x-ray source (6 MV Linac), multileaf collimators (MLCs), and a 30 cm × 30 cm × 30 cm water phantom located with its front surface at the beam isocenter. Simulations were performed with a source to surface distance (SSD) of 1,819 mm for nominal field sizes 2 cm × 2 cm, 6 cm × 6 cm, and 10 cm × 10 cm. Central axis percentage depth dose (PDD) and surface (or skin) doses at 70 μm depth were calculated by using high-resolution scoring voxels of 10 μm thickness. The results were compared with corresponding experimental data collected using MOSkin™ on the Australian MRI-Linac prototype system. The accurate modeling provides great detail into how the electron contamination is heavily confined and focused toward the beam central axis due to the presence of in-line magnetic field. This concentration significantly increases the skin dose up to 320% for the field size of 10 cm × 10 cm. For 2 cm × 2 cm and 6 cm × 6 cm, the surface skin dose is 128% and 217%, respectively, as compared to the skin dose in the absence of the magnetic field. The simulation results are in generally good agreement, ±10%, with previously collected experimental data for the same nominal field sizes. For the first time, detailed Geant4 Monte Carlo simulations of the electron contamination in the Australian MRI-Linac system have been performed and confirmed to be sufficiently accurate. These simulations will provide a solid framework for estimating the skin dose changes in more clinically relevant treatment plan scenarios that are envisaged in the near future.